Viewpoint: Reflections on the "Anti-Material Particle" in the Writings of Teilhard de Chardin and Swami Prabhupada - Rosen, Steven (Journal of Hindu-Christian studies, 2022)
Teilhard de Chardin's The Phenomenon of Man (1955) is a classic in the Christian tradition, while Easy Journey to Other Planets (1972), written by ISKCON's founder, A. C. Bhaktivedanta Swami Prabhupada, holds a similar position for devotees of the International Society for Krishna Consciousness. What has not yet been explored is the overlap and points of harmony between these two religious masterworks. Interestingly, both explore the nature of matter and spirit, using their own "scientific" terminology, and give readers food for thought: For example, consciousness, in its way, may indeed be quantifiable, and material and spiritual worlds can be understood (if not experienced) intellectually. In this essay, Steven Rosen briefly looks at the work of both authors, showing how the spiritual element might be articulated in terms that could also be appealing to the materialist.